Chemical Synthesis of Ubiquitin Chains. Issue 4 (2nd December 2015) - Hemantha, Hosahalli P.; Bondalapati, Somasekhar; Singh, Sumeet K.; Brik, Ashraf
Abstract : Chemical synthesis of complex biomolecules such as proteins is a challenging adventure, yet rewarding in driving various biochemical and biophysical research activities. Over the years, the refinement of peptide synthesis and invention of ligation methodologies have led to the successful synthesis of several complex protein targets. Ubiquitin bioconjugates, which are being studied intensively by many groups due to their involvement in numerous biological processes, represent a fine example where chemistry is greatly aiding these studies. In this article, we describe the synthetic routes and strategies to prepare different ubiquitin analogs with desired modifications, as well as di‐ubiquitin chains. © 2015 by John Wiley & Sons, Inc.